Low-residual-alkali high-nickel ternary positive electrode material as well as preparation method and application thereof
By replacing monohydrate lithium hydroxide with coated anhydrous lithium hydroxide, low-residual alkali high-nickel ternary cathode material is prepared, which solves the problem of excessive residual alkali on the surface of high-nickel ternary cathode material, and improves electrochemical performance and Cycling performance, and reduce production costs and simplify process flow.
Patent Information
- Application Number
- CN202411437962.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing high-nickel ternary cathode materials have high residual alkali content on the surface, resulting in poor electrochemical performance and cyclic performance, and unstable water washing process during the production process, affecting the material capacity and cyclic performance.
Use coated anhydrous lithium hydroxide instead of monohydrous lithium hydroxide as the raw material of the positive electrode material, and prepare low-residual alkali high-nickel ternary positive electrode material through the sintering process to avoid water washing process, inhibit moisture entry, prevent excess CO32-generated, and reduce residual Alkaline content.
The electrochemical performance and cyclic performance of high-nickel ternary cathode materials are significantly improved, production costs are reduced, production processes are simplified, and the stability of the materials is improved.
Smart Images

Figure CN119306268A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a low-residual-alkali high-nickel ternary positive electrode material with a lower residual alkali content on the surface, a preparation method and an application thereof. Background Art
[0002] Ternary cathode material LiNi x Co y Mn (1-x-y) The Ni extranuclear high-spin electron orbital in O2 does not overlap with the energy level of the oxygen extranuclear electron orbital. Compared with cobalt and manganese, it is easier to provide extranuclear electrons without destroying the layered structure. Increasing the Ni content can achieve higher capacity. When x>0.6, it is called a high-nickel ternary positive electrode material. Nickel-rich materials have higher capacity. However, the higher the Ni content, the more serious Li + / Ni 2+ Mixing seriously affects the diffusion of lithium ions, reduces the ionic conductivity of the material, and leads to poor chemical properties. Therefore, the prior art generally uses low-temperature decomposed lithium hydroxide as a lithium salt to prepare high-nickel ternary positive electrode materials. However, most of the lithium salts currently used are monohydrate lithium hydroxide. The lithium salts with crystal water not only have unstable main content, but the presence of crystal water is also the main factor inducing the formation of residual lithium on the surface. The LiOH / Li2CO3 remaining on the surface of the positive electrode material reacts complexly with the electrolyte, electrolyte and trace amounts of water to form a solid film that is unfavorable to electrochemistry, thereby causing a series of problems such as increased resistance, severe polarization, and decreased capacity. Summary of the invention
[0003] The present invention provides a low residual alkali high nickel ternary positive electrode material and a preparation method and application thereof, so as to solve the technical problems that the high nickel ternary positive electrode material produced by lithium hydroxide monohydrate has too high residual alkali on the surface, poor stability and easy to have adverse effects on the electrochemical performance and cycle performance of the battery.
[0004] In order to solve the above technical problems, the technical solution proposed by the present invention is: A method for preparing a low-residual-alkali-high-nickel ternary positive electrode material comprises the following operations: The high-nickel ternary precursor and the coated anhydrous lithium hydroxide are mixed evenly in proportion and then sintered. After the sintering is completed, the mixture is cooled to room temperature and sieved to obtain the low residual alkali high-nickel ternary positive electrode material; The coated anhydrous lithium hydroxide is prepared by the following method: The solvent and lithium hydroxide monohydrate are added into the reaction kettle, mixed and stirred evenly to obtain slurry; the slurry is put into a sand mill for ball milling, and then dried to obtain the coated anhydrous lithium hydroxide.
[0005] The design idea of the above technical solution is that the coated anhydrous lithium hydroxide has a large specific surface area, and a layer of organic matter is evenly coated on the surface of the lithium salt, which can protect the lithium salt, inhibit the entry of moisture in the air, and prevent excess CO3 2- By selecting coated anhydrous lithium hydroxide instead of monohydrate lithium hydroxide commonly used in the prior art as the raw material for the production of positive electrode materials, the surface of the high-nickel ternary positive electrode material can have a lower residual alkali content, and the water washing process can be eliminated, thereby avoiding the attenuation of the high-nickel material capacity and cycle performance caused by the instability of the water washing process, and preventing the jelly phenomenon from occurring during the homogenization process. While achieving the improvement of the electrochemical performance of the ternary positive electrode material, it also significantly reduces the production cost and simplifies the production process.
[0006] As a further preferred embodiment of the above technical solution, the molar ratio of the high-nickel ternary precursor to the coated anhydrous lithium hydroxide is (1~1.04):1.
[0007] As a further preferred embodiment of the above technical solution, the coated anhydrous lithium hydroxide particle size D50 is 15 μm~30 μm, and the specific surface area is 3.5 m 2 / g-4.5m 2 / g.
[0008] As a further preferred embodiment of the above technical solution, the sintering operation is to first heat the temperature to 300-350°C and keep it for 0.5-1h, then heat the temperature to 400-550°C and keep it for 0.5-2h; finally heat the temperature to 600-900°C and keep it for 10-20h. Compared with the traditional process, the calcination process of the present invention reduces the low-temperature dehydration stage, reduces the calcination temperature, and ensures the grain size of the product.
[0009] As a further preferred embodiment of the above technical solution, during the sintering process, the heating rate is 1-5°C / min.
[0010] As a further preferred embodiment of the above technical solution, the sintering operation is carried out in an oxygen atmosphere with an oxygen purity greater than or equal to 92%.
[0011] As a further preferred embodiment of the above technical solution, the sintering operation is carried out using a tubular furnace, a box furnace or a roller kiln.
[0012] As a further preferred embodiment of the above technical solution, a high-speed mixer or a ball mill is used to uniformly mix the high-nickel ternary precursor and the coated anhydrous lithium hydroxide.
[0013] As a further preferred embodiment of the above technical solution, the general formula of the high nickel ternary precursor is Ni x CoyMn (1-x-y) (OH)2, where 0.8≤x<1, 0<y<0.2.
[0014] Based on the same technical concept, the present invention also provides a low residual alkali and high nickel ternary positive electrode material, which is prepared by the preparation method described in the above technical solution.
[0015] As a further preferred embodiment of the above technical solution, the pH of the low residual alkali and high nickel ternary positive electrode material is less than 12.5, and the lithium carbonate content of the low residual alkali and high nickel ternary positive electrode material is less than or equal to 0.2%.
[0016] Based on the same technical concept, the present invention also provides a low residual alkali high nickel ternary positive electrode material for use in lithium ion batteries.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The high-nickel ternary positive electrode material of the present invention is prepared using coated anhydrous lithium hydroxide as a raw material. The coated anhydrous lithium hydroxide can inhibit the entry of moisture in the air and prevent excess CO3 2- The production of high nickel ternary positive electrode materials improves the stability of the positive electrode material, makes the surface of the high nickel ternary positive electrode material have a lower residual alkali content, improves the electrochemical properties of the ternary positive electrode material, reduces the production cost, simplifies the production process, and the battery prepared with the high nickel ternary positive electrode material of the present invention as the raw material has good rate performance and cycle performance.
[0018] The present invention will be further described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 This is a SEM' image of the coated anhydrous lithium hydroxide of Example 1 of the present invention; Figure 2 This is a SEM image of the high-nickel ternary positive electrode material of Example 1 of the present invention; Figure 3 This is the XRD diagram of the high nickel ternary positive electrode material of Example 1 of the present invention; Figure 4 The charge and discharge performance curve of the button battery prepared by the high-nickel ternary positive electrode material of Example 1 of the present invention; Figure 5 This is a rate performance curve of a button battery prepared with the high-nickel ternary positive electrode material of Example 1 of the present invention. DETAILED DESCRIPTION
[0020] The embodiments of the present invention are described in detail below with reference to the accompanying drawings, but the present invention can be implemented in many different ways as defined and covered by the claims.
[0021] The coated anhydrous lithium hydroxide used in each embodiment has a particle size D50 of 15 μm to 30 μm and a specific surface area of 3.5 m 2 / g-4.5m 2 / g.
[0022] After obtaining the low residual alkali and high nickel ternary positive electrode material in each embodiment, the pH or residual alkali test is performed on the ternary positive electrode material. The method is as follows: weigh 10.0±0.1 grams of powder, disperse it in 100±0.1 grams of deionized water, keep the water temperature at 25±0.2°C, stir for 10 minutes, obtain lucid water, test the lucid water with a pH meter, and read the pH value.
[0023] Embodiment 1: The low residual alkali high nickel ternary positive electrode material of this embodiment is prepared by the following method: (1) Weigh a certain amount of Ni 0.82 Co 0 .12 Mn 0 .06 (OH)2 high nickel ternary precursor and coated anhydrous lithium hydroxide fine powder, the molar ratio of high nickel ternary precursor to anhydrous lithium hydroxide is 1:1.03. The coated anhydrous lithium hydroxide is prepared by the following method: n-dodecane and lithium hydroxide monohydrate are added into a reaction kettle, the solid-liquid ratio of lithium hydroxide monohydrate to the solvent is 1:2, and the mixture is stirred evenly to obtain a slurry; the slurry is placed in a sand mill for ball milling for 2 hours, and then dried to obtain coated anhydrous lithium hydroxide; (2) Using a ball mill mixing device, the high nickel ternary precursor and the coated anhydrous lithium hydroxide fine powder are mixed evenly and placed in an atmosphere tube furnace for sintering. The sintering temperature of the first step is 300°C, the heating rate is 2°C / min, and the holding time is 1 hour, in order to allow the precursor to be fully decomposed; then the temperature is raised to 400°C at 2°C / min and kept for 1 hour; the purpose is to allow the coated anhydrous lithium hydroxide to be fully decomposed; then the temperature is raised to 750°C at 2°C / min and kept for 12 hours; the oxygen flow rate is maintained at 260ml / min during all sintering processes. The sintered product is naturally cooled and sieved to obtain the low residual alkali high nickel ternary positive electrode material of this embodiment.
[0024] The low residual alkali high nickel ternary positive electrode material of this embodiment is assembled into a button battery to evaluate its electrochemical performance. The assembly method is as follows: the low residual alkali high nickel ternary positive electrode material of this embodiment, Ketjen black, and polyvinylidene fluoride (PVDF) are weighed and mixed in a mass ratio of 90:5:5, and NMP is added and stirred for 4 hours to obtain a uniform slurry; then the slurry is evenly coated on aluminum foil with a thickness of about 100μm, and then placed in a blast drying oven, baked at 120°C for 12 hours, and cut into 12mm positive electrode sheets after drying. A metal lithium sheet with a diameter of 16mm is used as the negative electrode sheet, and a lithium battery 4.5V high voltage electrolyte and a polypropylene microporous membrane are used as the diaphragm. The button battery is assembled in a glove box filled with argon.
[0025] The assembled button cell was subjected to capacity test (3.0V-4.3V, 0.1C / 0.1C) and cycle test (3V-4.3V, 1C / 1C). The results are as follows: Figure 4 and Figure 5 shown.
[0026] Embodiment 2: The low residual alkali high nickel ternary positive electrode material of this embodiment is prepared by the following method: (1) Weigh a certain amount of Ni 0.82 Co 0 .12 Mn 0 .06 (OH)2 high nickel ternary precursor and coated anhydrous lithium hydroxide fine powder, the molar ratio of high nickel ternary precursor to anhydrous lithium hydroxide is 1:1.01. The coated anhydrous lithium hydroxide is prepared by the following method: n-dodecane and lithium hydroxide monohydrate are added into a reaction kettle, the solid-liquid ratio of lithium hydroxide monohydrate to the solvent is 1:2, and the mixture is stirred evenly to obtain a slurry; the slurry is placed in a sand mill for ball milling for 2 hours, and then dried to obtain coated anhydrous lithium hydroxide; (2) Using a ball mill mixing device, the high nickel ternary precursor and the coated anhydrous lithium hydroxide fine powder are mixed evenly and placed in an atmosphere tube furnace for sintering. The sintering temperature of the first step is 300°C, the heating rate is 2°C / min, and the holding time is 1 hour, in order to allow the precursor to be fully decomposed; then the temperature is raised to 400°C at 2°C / min and kept for 1 hour; the purpose is to allow the coated anhydrous lithium hydroxide to be fully decomposed; then the temperature is raised to 750°C at 2°C / min and kept for 12 hours; the oxygen flow rate is maintained at 260ml / min during all sintering processes. The sintered product is naturally cooled and sieved to obtain the low residual alkali high nickel ternary positive electrode material of this embodiment.
[0027] The low residual alkali high nickel ternary positive electrode material of this embodiment is assembled into a button battery to evaluate its electrochemical performance. The assembly method is as follows: the low residual alkali high nickel ternary positive electrode material of this embodiment, Ketjen black, and polyvinylidene fluoride (PVDF) are weighed and mixed in a mass ratio of 90:5:5, and NMP is added and stirred for 4 hours to obtain a uniform slurry; then the slurry is evenly coated on aluminum foil with a thickness of about 100μm, and then placed in a blast drying oven, baked at 120°C for 12 hours, and cut into 12mm positive electrode sheets after drying. A metal lithium sheet with a diameter of 16mm is used as the negative electrode sheet, and a lithium battery 4.5V high voltage electrolyte and a polypropylene microporous membrane are used as the diaphragm. The button battery is assembled in a glove box filled with argon.
[0028] The assembled button battery was subjected to a capacity test (3.0V-4.3V, 0.1C / 0.1C), and the result was 211.5mAh / kg.
[0029] The low residual alkali and high nickel ternary positive electrode materials of Example 1 and Example 2 were tested for alkali value, and the results are shown in Table 1.
[0030] Table 1. Alkalinity test results of ternary cathode materials in various embodiments
[0031] The above are only preferred embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various changes and modifications. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the protection scope of the present application. The above are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. For those skilled in the art, improvements and changes obtained without departing from the technical concept of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a low residual alkali high nickel ternary positive electrode material, characterized in that: The following operations are included: The high-nickel ternary precursor and the coated anhydrous lithium hydroxide are mixed evenly in proportion and then sintered. After the sintering is completed, the mixture is cooled to room temperature and sieved to obtain the low residual alkali high-nickel ternary positive electrode material; The coated anhydrous lithium hydroxide is prepared by the following method: The solvent and lithium hydroxide monohydrate are added into the reaction kettle, mixed and stirred evenly to obtain slurry; the slurry is put into a sand mill for ball milling, and then dried to obtain the coated anhydrous lithium hydroxide.
2. The method for preparing the low residual alkali high nickel ternary positive electrode material according to claim 1, characterized in that: The solid-liquid ratio of the lithium hydroxide monohydrate to the solvent is 1:(2-5), and the ball milling time is 0.5-2h.
3. The method for preparing the low residual alkali high nickel ternary positive electrode material according to claim 1, characterized in that: The molar ratio of the high-nickel ternary precursor to the coated anhydrous lithium hydroxide is (1-1.04):
1.
4. The method for preparing the low residual alkali high nickel ternary positive electrode material according to claim 1, characterized in that: The sintering operation is to first heat the temperature to 300-350° C. and keep it for 0.5-1 hour, then heat the temperature to 400-550° C. and keep it for 0.5-2 hours; and finally heat the temperature to 600-800° C. and keep it for 10-20 hours.
5. The method for preparing the low residual alkali high nickel ternary positive electrode material according to claim 4, characterized in that: During the sintering process, the heating rate is 1-5°C / min.
6. The method for preparing the low residual alkali high nickel ternary positive electrode material according to claim 1, characterized in that: The sintering operation is carried out in an oxygen atmosphere, and the oxygen purity is greater than or equal to 92%.
7. The method for preparing the low residual alkali high nickel ternary positive electrode material according to claim 1, characterized in that: The general formula of the high nickel ternary precursor is Ni x CoyMn (1-x-y) (OH)2, where 0.8≤x<1, 0<y<0.
2.
8. A low residual alkali high nickel ternary positive electrode material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7.
9. The low residual alkali high nickel ternary positive electrode material according to claim 8, characterized in that: The pH of the low residual alkali and high nickel ternary positive electrode material is less than 12.5, and the lithium carbonate content of the low residual alkali and high nickel ternary positive electrode material is less than or equal to 0.2%.
10. Use of the low residual alkali and high nickel ternary positive electrode material according to claim 8 or 9 in a lithium ion battery.
Citation Information
Patent Citations
Coated modified anhydrous lithium hydroxide and preparation method thereof
CN112299452A
Water-washing-free coating method for high-nickel positive electrode material
CN113809287A
Cited By
Multinary material, cathode material, and battery
CN122800605A